2008
DOI: 10.1089/dna.2007.0715
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin (IL)-12 and IL-27 Gene Polymorphisms with Chronic Obstructive Pulmonary Disease in a Chinese Population

Abstract: The pathogenesis of chronic obstructive pulmonary disease (COPD) is not fully understood, and environment and genetic factors have been investigated. Moreover, cytokine genes play an important role in COPD pathogenesis. However, the molecular mechanism of COPD induced by the factors is still unknown. The present study was undertaken to clarify a role of interleukin (IL)-12 16974A/C and IL-27 4730T/C, -964A/G, and 2905T/G polymorphisms in Chinese subjects with COPD. Polymerase chain reaction/restriction fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 15 publications
1
37
0
1
Order By: Relevance
“…Regarding COPD, Huang and colleagues showed that two IL27 polymorphisms, c.-964A/G (rs153109, LD with rs181206, r 2 = 0.49 in HapMap3 CEU; r 2 = 0.32 in HapMap3 Japanese individuals from Tokyo, Japan, and Han Chinese individuals from Beijing, China [JPT1CHB]) and g.2905T/G (rs17855750, LD with rs181206, r 2 = 0.03 in HapMap3 CEU, r 2 = 0.016 in HapMap3 JPT1CHB), are associated with COPD susceptibility in a Chinese population (63). Cao and colleagues reported higher levels of IL27 in the sputum and plasma of patients with COPD than in those of healthy control subjects, with a negative correlation between IL27 levels and FEV 1 in patients with COPD (64).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding COPD, Huang and colleagues showed that two IL27 polymorphisms, c.-964A/G (rs153109, LD with rs181206, r 2 = 0.49 in HapMap3 CEU; r 2 = 0.32 in HapMap3 Japanese individuals from Tokyo, Japan, and Han Chinese individuals from Beijing, China [JPT1CHB]) and g.2905T/G (rs17855750, LD with rs181206, r 2 = 0.03 in HapMap3 CEU, r 2 = 0.016 in HapMap3 JPT1CHB), are associated with COPD susceptibility in a Chinese population (63). Cao and colleagues reported higher levels of IL27 in the sputum and plasma of patients with COPD than in those of healthy control subjects, with a negative correlation between IL27 levels and FEV 1 in patients with COPD (64).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, through a number of genetic approaches, it has been found that there is an association of COPD susceptibility and gene polymorphisms in the T H 17 effector cytokine IL-17F and the T H 17 regulatory cytokine IL-27. 98,99 This evidence for the involvement of T H 17 cells in COPD is still in early stages of understanding, however, the characteristics of COPD pathogenesis are fitting with the known pathways of T H 17 cells. 96 effective than other approaches, and their efficiency has been demonstrated in a number of other disease settings.…”
Section: Manipulation Of T H 17 Responsesmentioning
confidence: 96%
“…Polymorphisms in the IL-27p28 gene have been associated with risk of inflammatory bowel disease 131 , RA 132 , asthma 130 , allergic rhinitis 133 , chronic obstructive pulmonary disease 134 , and with protection of ulcerative colitis 135 . In a Chinese casecontrol study, an association of atrial septal defects and ventricular septal defect with the G allele of rs153109 polymorphism was reported; no association was found with the rs17855750 polymorphism 136 .…”
Section: Il-27p28 Genementioning
confidence: 99%